Collecting and Managing Tax Debt in Poland - Hybka, Małgorzta Magdalena (Windykacja i zarządzanie zaległościami podatkowymi w Polsce, 2025)
Aim: The paper highlights the formation of tax debt, compares it among EU member states, examines certain factors contributing to its accumulation, and evaluates measures taken to manage tax debt collection. Methodology: Indicators from OECD publications were utilized to evaluate the accumulation and recovery of tax arrears. A comparative analysis juxtaposed their operational performance in EU member states, and a multiple regression model was employed to estimate the effect of independent variables on tax debt accumulation in Poland. Results: Some countries continuously face the problem of skyrocketing tax arrears, while others are relatively successful in tax collection. Rapidly accumulating tax debt has, for many years, posed a challenge to the Polish tax administration, as it is relatively high in Poland compared to other EU member states. Implications and recommendations: For many years, Poland has predominantly applied conventional methods to deal with tax debtors. Some EU countries have successfully introduced more innovative tools, leading to a decrease in tax debt and improvements in its structure to enhance recovery, including, inter alia, a behavioral approach. Originality/value: This paper attempts to uncover a dimension of tax collection that is often overlooked in scientific research and to answer the question of what happens when tax is properly assessed but not paid to the tax authorities. Tax debt accumulation is relatively rarely discussed, and methods of its analysis are sparse in economic literature.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 1, s. 46-58
Keywords: tax debt; tax arrears; tax management; zaległości podatkowe; dług podatkowy; zarządzenie podatkami